The Effectiveness of Digital Population Identity on the Public in the City of Bandung in 2023-2024 - Akhyar, M Nur; Redjo, Samugyo Ibnu; Kartini, Dede Sri (Journal of Governance and Social Policy, 2025)
Digital transformation in population administration is an important part of the modernization of public services in Indonesia, including in the city of Bandung. This study analyzes the effectiveness of the implementation of Digital Population Identity (IKD) in 2023-2024 using Robert B. Duncan's theory of effectiveness, which includes three main indicators: goal achievement, integration, and adaptation. The results show that the realization of the use of IKD is still low, with an achievement of only 1.91% in January 2024, far below the target of 25%. The socialization of the program is still limited to certain groups, while the general public's understanding of IKD is not optimal. In addition, the limitations of digital infrastructure and human resources are the main challenges in the implementation of this system. Therefore, a more comprehensive strategy is needed through increasing socialization, strengthening infrastructure, and increasing the capacity of apparatus in managing digital systems. With these steps, it is hoped that IKD can be more effective in improving the efficiency and accessibility of population services in the city of Bandung